Post-extraction: from sand to fabricated lakes - Karle, David (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2024)
Beyond urban boundaries, radical transformations in land use, infrastructure, and ecology, termed as manufactured sites or operational landscapes, sustain urban societies through resource extraction. While historically overlooked, these processes shape urban growth and pose challenges in fragile states. Despite the focus on celebrity materials such as coal and oil, historically, non-celebrity resources such as sand and gravel have also played vital roles. Recognizing the significance of peri-urban landscapes, particularly in regions such as the U.S. Great Plains is crucial to balancing design, extraction, and ecology. The peri-urban sand and gravel extraction sites above the Ogallala Aquifer are filling with groundwater and result in recreational and residential lakes that reshape the urban edges. This essay explores the transformation of these post-extraction sandpit lakes, highlighting opportunities for new design interventions and emphasizing the need for responsible interdisciplinary practices that balance human needs with ecological concerns.
Keywords: Extraction; Urbanization; Post-Extraction; Resources; U.S. Great Plains; Nebraska